The Weihai Observatory Search for Close-in Planets Orbiting Giant Stars. (4th January 2016) - Wittenmyer, Robert A.; Gao, Dongyang; Ming Hu, Shao; Villaver, Eva; Endl, Michael; Wright, Duncan
Abstract: Planets are known to orbit giant stars, yet there is a shortage of planets orbiting within ∼0.5 AU ( P ≲ 100 days). First-ascent giants have not expanded enough to engulf such planets, but tidal forces can bring planets to the surface of the star far beyond the stellar radius. So the question remains: Are tidal forces strong enough in these stars to engulf all the missing planets? We describe a high-cadence observational program to obtain precise radial velocities of bright giants from Weihai Observatory of Shandong University. We present data on the planet host Beta Gem (HD 62509), confirming our ability to derive accurate and precise velocities; our data achieve an rms of 7.3 m s -1 about the Keplerian orbit fit. This planet-search program currently receives ∼100 nights per year, allowing us to aggressively pursue short-period planets to determine whether they are truly absent.